Deconstructing the Binary Tropes of Gender Discrimination in Shazaf Fatima Haider's How It Happened - Ansar, Mohammed; Sami, Muhammad (Educalitra: English Education, Linguistics, and Literature Journal, 2025)
This paper seeks to analyze Shazaf Fatima Haider’s How It Happened using postcolonial feminist framework and through close textual analysis, deconstructing the binarism of gender discrimination in the novel. Women within the traditional patriarchal structures are presented through Dadi’s prescriptive role as she plays in the life of women through putting across structured belief system which dominates women’s existence. Dadi's admonitions, such as the notion that "good girls marry boys of their mothers’ choice," reinforce the binary division between obedient women and rebellious ones, stripping women of agency in both marriage and emotional autonomy. These Social, institutional and cultural norms served and depicted women as only valuable in the kitchen or as sex objects that silence women and value them in comparison to men. By caricaturing these gender roles, Haider addresses social and institutional unfreedom for women still judged by society as unfit if they don’t conform to traditional gender roles. Mainstreaming the conflict between women’s power and desire for freedom, Haider’s novel raises questions about colonial gendered perspectives, opposing their continuation, and calls to rethink these constructions to free women from these male-dominate definitions. Thus, through such binaries, How It Happened helps to deepen a conversation on gender, culture and postcolonial feminism.